EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen